Application of hydrophilic interaction liquid chromatography for the quantification of succinylcholine in Active Pharmaceutical Ingredient and medicinal product. Identification of new impurities of succinylcholine chloride - Szterk, Arkadiusz (Heliyon, 2018)
A new method, using hydrophilic interaction chromatography (HILIC), for quantification of succinylcholine and impurities in Active Pharmaceutical Ingredient (API), as well as in the medicinal product, was developed. Additionally, the new impurities in API were discovered using ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-QTOF) technique. The substances were quantified with the application of a UV detector (λ = 214 nm). Chromatographic separation was performed isocratically with the application of 30% phosphate buffer (pH 4,0; 0.05 M) in ACN as a mobile phase. A major feature of the developed method is a very high resolution (Rs > 3), between succinylcholine and its main impurity - succinylmonocholine, whereas the width of peak bands does not exceed 0.7 min. A low value of limits of detection (LOD) were obtained for succinic acid, succinylmonocholine and for succinylcholine, which amounted to 2.4, 6.0 and 11.5 μg ml(−1), respectively. Another feature of the developed method is linearity in a very wide range of concentrations: 7.3 μg ml(−1) – 670 μg ml(−1) amounting to R(2) = 0.999. The recovery provided by this method at three different fortification levels for all analytes remained within the following range: 95.7 – 98.9 %. Intra-day and inter-day precision remained within the following range: 1.0 – 5.9 % coefficient of variation (CV), whereas accuracy within the range: −1.3 – 6.3. The developed method of hydrophilic interactions made it possible to quantify two new impurities, probably originating from the synthesis of an API: [2-(trimethylaminium)ethyl]-[2ʹ-(trimethylaminium)vinyl] succinate and [2-(dimethylamino)etyl]-[2ʹ-(trimethylaminium)etyl] succinate, which were identified and described for the first time. In addition, a physicochemical form of peak doublet described in the USP as impurities was studied and it was demonstrated that these peaks are the result of the specific physicochemical interactions in ion pair chromatography.